Social costs of business enterprise - Kapp, Karl William (Bombay ; New York : Asia Pub. House, 1963)
The change of title to social costs of Business Enterprise is intended to express more explicitly the affinity of our analysis to the intellectual tradition of that branch of institutional economic theory which has stressed not only the cumulative character of social causation and the need for objective criteria of social welfare for the appraisal of the social efficiency of economic systems, but also the importance of raising the question of the quality of human life and behavior under different institutional arrangements.
Includes bibliographical footnotes and index.
hza 26/07/2018
Loan
Keywords: Business enterprise; Social-cost.